Strengthening Organizational Resilience through Visionary Leadership and Trust: A Study of Private Universities in Indonesia (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to examine the strategic contribution of visionary leadership and trust to organizational resilience in Indonesian private higher education institutions. Specifically, it investigates the magnitude of influence these factors have on building institutional resilience amidst the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era challenges. Method: Employing a POP-SDM (Resource Strengthening Management) approach, this research utilizes path analysis and SITOREM methods. Data were collected through questionnaires, interviews, and document analysis from private universities across Indonesia. The study focuses on measuring the direct and indirect effects of visionary leadership and trust on organizational resilience. Results: The findings reveal that visionary leadership has a significant positive influence on organizational resilience, with trust serving as a crucial mediating factor. The magnitude of effect demonstrates that institutions with stronger visionary leadership and higher levels of trust exhibit substantially greater resilience capabilities. The integrated model explains a substantial proportion of variance in resilience outcomes, providing empirical evidence for the strategic importance of these factors. Novelty: This research introduces the POP-SDM approach adapted for higher education contexts, offering a comprehensive framework for strengthening organizational resilience. The study contributes to theoretical literature by integrating visionary leadership, trust, and resilience in the specific context of Indonesian private universities facing unique challenges in the VUCA era.